Does zebra mussel (Dreissena polymorpha) represent the freshwater counterpart of Mytilus in ecotoxicological studies? A critical review. (January 2015) - Binelli, A.; Della Torre, C.; Magni, S.; Parolini, M.
Abstract: One of the fundamentals in the ecotoxicological studies is the need of data comparison, which can be easily reached with the help of a standardized biological model. In this context, any biological model has been still proposed for the biomonitoring and risk evaluation of freshwaters until now. The aim of this review is to illustrate the ecotoxicological studies carried out with the zebra mussel Dreissena polymorpha in order to suggest this bivalve species as possible reference organism for inland waters. In detail, we showed its application in biomonitoring, as well as for the evaluation of adverse effects induced by several pollutants, using both in vitro and in vivo experiments. We discussed the advantages by the use of D. polymorpha for ecotoxicological studies, but also the possible limitations due to its invasive nature. Graphical abstract: Highlights: Dreissena polymorpha as possible reference organism for inland waters. Its application in biomonitoring of some freshwater ecosystems worldwide. Use of this biological model in the biomarker approach and omics techniques. Abstract : We discuss the advantages made by Dreissena polymorpha for ecotoxicological studies in freshwaters bearing in mind also the limitations due to its invasive nature.